Aplicação do resíduo de bauxita como fonte de Al2O3 e Fe2O3 na preparação de clínqueres de cimentos portland - Lourenço, Rafaela Roberta (2013)
During the past decades, the bauxite residue (BR) generated in the aluminium production was considered unusable waste. However, the difficulties and the costs associated with the residue management and storage have motivated companies to invest in innovative research to find economical and environmentally safe applications for the BRin order to reduce the volume of waste stored. In this context, the building industry offers a promising application for BR. This sort of residue could be used in large quantities in the production of Portland cement, one of the most important materials in this sector. The partnership between the aluminium and cement producers might benefit both areas, opening a great opportunity to move towards sustainable development and to minimize environmental impacts. Therefore, the aim of this study was to evaluate the use of BR as an alternative source of Al2O3 and Fe2O3 in Portland cements clinker. Four formulations were developed: one without BR, which was used as a reference composition (C1),and three others containing 3wt%(C2)7 wt%(C3) and13 wt% (C4) of BR. As the main phases-C3S, C2S, C3A e C4AF- were detected in the produced clinker, it was clear that BR addition did not affect the mineralogical composition. Nevertheless, BR contents equal or greater than7wt% resulted in the formation of C3A doped with Na, which has an orthorhombic structure. Based on the quantitative X ray diffraction results and on the phase s morphology it was found that although the presence of residue has altered the chemical composition of the clinker, the mechanical behavior of the material was not affected. The mortars prepared with these clinkers reached satisfactory compressive strength and C4 materials had values of 39MPa. The results demonstrated that the presence of the BR did not affect negatively the quality of the produced material which indicates an interesting potential application for the BR.